Assimilation of Technologies vs. Technological maturity of industry 4.0: the case of the dairy processing sector in Poland - Młody, Michał; Sajdak, Maja; Wójcicki, Krzysztof (Management and Production Engineering Review, 2026)
The transition toward Industry 4.0 in the agri-food sector necessitates a nuanced understanding of how digital technologies are assimilated within operational and strategic contexts. This study investigates the relationship between technology assimilation and technological maturity in the dairy processing industry - an often-overlooked yet critical segment of the food production value chain. Drawing on a CATI survey of 68 Polish dairy manufacturing companies, we operationalized (5-point Likert scale) assimilation and maturity through principal component analysis (PCA), identifying two core dimensions of assimilation (integration and cybersecurity; digital competencies and data analytics) and four dimensions of maturity (digital technologies and data use; process automation and sustainability; IT flexibility; AI). The results reveal strong correlations between strategic integration of digital transformation and maturity in process automation and sustainability, as well as between digital skills and IT system adaptability. Notably, AI remains at an early adoption stage, reflecting infrastructural and human capital constraints. Our findings underscore the need for aligned strategy, secure digital environments, and workforce development, and support phased digitalization with targeted training and infrastructure investment.